Neuregulin-4 attenuates diabetic cardiomyopathy by regulating autophagy via the AMPK/mTOR signalling pathway - Wang, Hongchao; Wang, Lijie; Hu, Fuli; Wang, Pengfei; Xie, Yanan; Li, Fang; Guo, Bingyan (Cardiovascular diabetology, 2022)
Background Diabetic cardiomyopathy is characterized by left ventricle dysfunction, cardiomyocyte apoptosis, and interstitial fibrosis and is a serious complication of diabetes mellitus (DM). Autophagy is a mechanism that is essential for maintaining normal heart morphology and function, and its dysregulation can produce pathological effects on diabetic hearts. Neuregulin-4 (Nrg4) is an adipokine that exerts protective effects against metabolic disorders and insulin resistance. The aim of this study was to explore whether Nrg4 could ameliorate DM-induced myocardial injury by regulating autophagy. Methods Four weeks after the establishment of a model of type 1 diabetes in mice, the mice received Nrg4 treatment (with or without an autophagy inhibitor) for another 4 weeks. The cardiac functions, histological structures and cardiomyocyte apoptosis were investigated. Autophagy-related protein levels along with related signalling pathways that regulate autophagy were evaluated. In addition, the effects of Nrg4 on autophagy were also determined in cultured primary cardiomyocytes. Results Nrg4 alleviated myocardial injury both in vivo and in vitro. The autophagy level was decreased in type 1 diabetic mice, and Nrg4 intervention reactivated autophagy. Furthermore, Nrg4 intervention was found to activate autophagy via the AMPK/mTOR signalling pathway. Moreover, when autophagy was suppressed or the AMPK/mTOR pathway was inhibited, the beneficial effects of Nrg4 were diminished. Conclusion Nrg4 intervention attenuated diabetic cardiomyopathy by promoting autophagy in type 1 diabetic mice. Additionally, Nrg4 induced autophagy via the AMPK/mTOR signalling pathway.